A critical review in Fenton-like approach for the removal of pollutants in the aqueous environment - Aref Shokri; Mahdi Sanavi Fard (Environmental Challenges, 2022)
Demographic changes, sustainable enhancement, accelerated urbanization, climatic fluctuations, scarcity of recourses, and the advent of different kinds of refractory pollutants are some of the major water-related challenges which require to be effectively treated with state-of-the-art methods. In the view of current scenario, the presence of some bio-resistant organic compounds causes a significant restriction for traditional wastewater treatment methods. As an alternative for treating various kinds of liquid wastewaters, Fenton-like and Fenton approaches besides their integration, show a lot of promise. For many Fenton-based processes, different kinds of catalytic iron species have been utilized for in situ generation of OH• through the catalytic decomposition of H2O2, which its activation mechanism is significantly related to the catalyst nature and compositions. However, a major challenge for iron-dependent Advanced Oxidation Processes (AOPs) is providing a harsh acidic environment to avoid iron precipitation. In order to overcome this challenge, various iron-free catalysts with different redox states including chromium, copper, silver, cerium, manganese, aluminum, cobalt, ruthenium and polyoxometalates are explored. Hence, this paper comprehensively review aforementioned catalysts mechanisms, their reactivity against H2O2 activation and highlights the practical restrictions that affect their environmental applications. Also, some crucial parameters which governs process efficiency such as temperature, catalyst dosage, H2O2 dosage, and pH in both homogeneous and heterogeneous Fenton-like reactions are investigated. Finally, photo-Fenton-like, electro-Fenton-like, cavitation-Fenton-like and microwave-Fenton-like methods for pollutant degradation in wastewater are briefly discussed.